Student Attendance System (e-StAS) / Nurdiana Ezani Nordin - Nordin, Nurdiana Ezani (2015)
Nowadays, in managing and recording the student attendance data are still less effective and not systematic. This is due to the implementation of traditional or manual recording and managing method. Student Attendance System (e-StAS) is being proposed to ease the process of recording and managing the attendance data. E-StAS is a web-based system technology where will help the lecturer and HEA staff to record and manage data easier, faster and more efficiently. This system will allow users to generate report and calculate student attendance percentage. Waterfall methodology is used in order to help in developing this system. This methodology consists of five phases which are Analysis, Design, Development, Testing and Evaluate phase. Thirty respondents completed a questionnaire designed to measure the navigation, ease of use, usefulness, ease of learning and user satisfaction. Thus, the result shows that this system is easy to use with the highest mean value of 4.34 (SD; 0.597). On top of that, an interview session with an expert has been done in order to get their review regarding the system performance and usability. As a conclusion, this e-StAS will give more benefits toward the users and hopefully it can contribute further in the process of managing and recording the student attendance data.